Green innovation is an introduction to promoting sustainable Manufacturing : an analytical study of the opinions of a sample of workers in Al Karwanji Group in Kirkuk. (NTU journal for Administrative and Human Sciences (JAHS), 2023)
Currently, urgent challenges such as the acceleration of technological progress, resourcescarcity, globalization, and sustainability are forcing companies to redefine theirmanufacturing processes and create products that reduce waste, preserve resources, andreduce emissions and harmful pollutants through a wide range of strategies and practices.Therefore, this research aims to use the green innovation approach to promotesustainable manufacturing, in light of the field problem represented by the weakness ofthe manufacturing approach aimed at meeting environmental requirements representedby sustainable manufacturing as a window that qualifies it to stay and continue in thecompetitive market, with the aim of promoting the dimensions of green innovation in thepractices of the researched company, the Krongi group of companies. The importance ofthe research is reflected in the questions raised, one of the most important of which is:what is the level of the impact of green innovation on sustainable manufacturing in theresearched company? Data was collected through a survey from a random sample of 92managers and employees of Krongi Company for carbonated beverages, mineral water,and juices in Kirkuk. The response rate was (96.84%) with 92 survey forms that werestatistically analyzed using SPSS Ver-28. Several conclusions were reached, the mostimportant of which was the validity of the assumptions included in the research throughverifying the existence of a significant correlation between the research variables and thepresence of a significant positive effect of green innovation and its dimensions onsustainable manufacturing, which reflects the interest of the researched company inadopting these dimensions and the compatibility of the nature of the company's work andresearch variables. Several proposals were presented, the most important of which aredisseminating the concepts of green innovation and sustainable manufacturing and theirprocedures among individuals working in the researched company, paying greaterattention to embracing green innovation through searching for new and innovativetechnologies and methods that can help reduce waste, preserve resources, and reduce theenvironmental impact of manufacturing processes in the researched company, whichenables companies to improve their competitiveness, reduce operating costs, and benefitfrom markets.